Merdeka! Learn the History of Malaysia via 2D Interactive Game - Syed Hussin, Syed Mohamad Khaidir; Zaini, Hazrati (2020)
As the time goes by, the history of Malaysia tends to be forgotten each day among Malaysian. History is one of the important things that need to be known by the whole civilization in order to foster a spirit of patriotism. Students were also having difficulties in studying the history subject because of its long, boring and repeatable content. According to the preliminary study, majority of the students agreed that the used of text book or other printed material are less attractive compare to using technology that consist of colourful images and sound. Most of students only study in order to get good mark in an examination. As a result, they do not properly understand the knowledge and message that are given from the subject. The purpose of this study to design an interactive platform where student will be able to learn about the history of Malaysia, develop an enjoyable experience of learning Malaysia's history via gaming, and to evaluate the enjoyment of the historic-themed 2D game. This project used Game Development Life Cycle methodology for the development of the project to smoothen the process and flow toward the construction of the project. To evaluate the user’s enjoyment, this project applied E- Game Flow questionnaire. The result of the evaluation shows the game received 72% level of agreeability. Future work of this game is to improve the overall graphic of the game and add more engagement of the character such as fighting and climbing to provide a better playing experience.